Ab-initio combined Calphad approach to the phase equilibria in the ternary Ti-Mo-N system (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The ternary Ti-Mo-N system is an important material that has found applications as a surface coating, hardener, and wear and corrosion protective coating. Knowledge of phase equilibria, phase transformations and phase stabilities of this alloy is important to realize its potential application. In this paper, ab-initio calculations along with Calphad modeling were used to determine the Gibbs energies of all phases existing in this industrially important system. The calculated Gibbs energies were used to calculate and construct the phase diagrams and thermodynamic properties of the Ti-Mo-N system. The present model is in good agreement with literature values. The results of this work can be used as foundation for future investigations on the Ti-Mo-N system as well as basis for practical industrial applications.
Keywords: ab initio; Caphad; phase diagram; Mo; Ti; N